1984
DOI: 10.1007/bf00583882
|View full text |Cite
|
Sign up to set email alerts
|

Calcium fraction correlating with contractile force of ventricular muscle of guinea-pig heart

Abstract: Ca shifts in the isolated, perfused ventricular muscle of guinea-pig hearts were investigated with the aid of 45Ca under the conditions of complete equilibration of preparations with the isotope-containing solution. In some series of experiments total Ca content was also measured by means of atomic absorption spectrophotometry. The content of 45Ca at the end of 70 min equilibration period during which the ventricles were stimulated at a rate of 60/min was 1.66 +/- 0.09 mmol/kg w.w. This content dropped to 0.42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Hence we proposed that Ca 2 fraction might be intimately involved in the mechanism of slow, force-frequency relations as already postulated by Chapman and Niedergerke for the frog heart (5). Results of the comparative experiments performed previously on the guinea pig (17,12) and rat (11) ventricular *) This study was supported by the grant CPBR, 11.6 myocardium and on guinea pig atrial muscle (16) have shown that the response of the volume of Ca2 fraction to the prolonged rest and post-rest stimulation parallel the respective responses of CF whose pattern varies from species to species, and from one part of the heart to another.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Hence we proposed that Ca 2 fraction might be intimately involved in the mechanism of slow, force-frequency relations as already postulated by Chapman and Niedergerke for the frog heart (5). Results of the comparative experiments performed previously on the guinea pig (17,12) and rat (11) ventricular *) This study was supported by the grant CPBR, 11.6 myocardium and on guinea pig atrial muscle (16) have shown that the response of the volume of Ca2 fraction to the prolonged rest and post-rest stimulation parallel the respective responses of CF whose pattern varies from species to species, and from one part of the heart to another.…”
Section: Introductionmentioning
confidence: 85%
“…Experiments were performed on isolated, vascularly perfused ventricles of hearts from New Zealand white rabbits (1.4-1.9 kg), according to the methods described in detail elsewhere (17,12). Briefly, the hearts were isolated and perfused by Langendorff method with Tyrode solution of the following composition (in mM): NaCI, 137; KCI, 7.40; CaCI2, 1.80; MgCI,, 1.05; NaH2PO4, 0.43; NaHCOs, 11.90; glucose 11.00. pH of the solution when gassed with 5% CO2 in 95% 02 was 7.35.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hearts were perfused with the 45Ca-containing solution for the next 60 min and stimulated at the rate of 60/min, which assured complete equilibration of the tissue Ca 2t exchangeable with 45Ca (19). Thereafter, in all experiments, stimulation was stopped and the heart was perfnscd with one of the solutions listed below: A) Tyrode solution containing 4SCa and 0.1 mM vanadate; B) Tyrode solution containing 0.1 mM vanadate (no 4SCa); C) No Na t solution containing (in mM): CaCI2 1.8; MgCI 2 1.05; KCI 7.8; glucose i1; Tris-HC1 10; sucrose 243; vanadate 0.1 and 45Ca; D) C (no Na t) solution without 45Ca; E) Low Ca 2+ solution containing (in mM): free Ca 2+ 0.01; free Mg 2+ 1; free K + 7.5; free Na § 140; TRIS-HCI 10; EGTA 0.1; glucose 11; vanadate 0.1, and 45Ca; F) Low Ca 2t solution (E) without 45Ca; G) Low Ca 2t, no Na + solution: the E solution in which 1 mM NaCI was substituted by 1.84 mM sucrose (22); and H) Low Ca 2+, no Na + solution: the G solution without 45Ca.…”
Section: Solutmns and Protocolsmentioning
confidence: 99%
“…The transsarcolemmal Ca 2+ fluxes remain a subject of wide interest (3,13,16,18,19,23,25). One approach to the investigation of these Ca 2 § fluxes is by use of the isotope 45Ca.…”
Section: Introductionmentioning
confidence: 99%